Entre o diatônico e o cromático: Giovanni Scaramella e a organologia da flauta - André dos Santos Mendes (2024)
Giovanni Scaramella (1823-1857) was a 19th century Napolitan flute player and composer who lived in Brazil. Although Scaramella has been almost forgotten by the flute literature, he had held the most important workplaces for a flute player during the 1850’s in the capital of the Brazilian empire. On the other hand, recent research has associated his name with Saverio Mercadante (1795-1870), with whom Scaramella studied composition in the Conservatory of San Pietro a Majella in Naples, when a flourishing flute culture was emerging there. Based on research in Napolitan and Brazilian 19th century newspaper, also in the analysis of two of his compositions for flute, in Entre o diatônico e o cromático: Giovanni Scaramella e a organologia da flauta we aim to elucidate aspects of Scaramella’s life and work, discussing his use of both Boehm and simple system of flutes, and revealing his remarkable presence in the context of cultural transferences between Rio de Janeiro and Naples. The social network developed in Naples Conservatory during the 1840’s had later connections with Rio de Janeiro, when Scaramella was privileged as soloist and even acted in a diplomatic mission in Paris, contracting new musicians and singers for the opera house in Brazil. In this context, we even observe the similarities between the flute classes of Naples and Rio de Janeiro Conservatory. The analysis of his compositions shows the possibility of both Boehm and the simple system flutes, which means an experience with the system that after became the one for the modern concert flute, and a link to the traditional flute from late 18th and early 19th century. Our analysis provides information for performances with historical flutes.